PENGARUH KUALITAS PRODUK, CITRA MEREK, PERSEPSI HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN HONDA VARIO (Studi Empiris Pada Dealer Cendana Wangi Pekalongan) - Gilang Dipa R., 12.05.51.0046; Soliha, Euis (Students' Journal of Economic and Management, 2019)
This study seeks to examine the Effect of Product Quality, Brand Image, Price Perception, and Promotion on Honda Vario Purchase Decisions at the Cendana Wangi Dealer in Pekalongan.This study used a sample of 78 respondents who decided to buy Honda Vario at the Pekalongan Wangi Sandalwood Dealer using a multiple linear regression analysis tool. Based on the results of the study indicate that product quality has a positive and significant effect on purchasing decisions. The better the quality of the product, the purchasing decision increases, the brand image does not affect the purchasing decision, the price perception does not affect the purchasing decision, the promotion has a positive and significant effect on the purchasing decision. The more active promotions are made, the purchasing decisions increase.